Preventing Occupational Hearing Loss: 50 Years of Research and Recommendations from the National Institute for Occupational Safety and Health - Themann, Christa L.; Masterson, Elizabeth A.; Peterson, Jeffrey Shawn; Murphy, William J. (Seminars in Hearing, 2023)
For more than 50 years, the National Institute for Occupational Safety and Health (NIOSH), part of the United States (U.S.) Centers for Disease Control and Prevention (CDC), has been actively working to reduce the effects of noise and ototoxic chemicals on worker hearing. NIOSH has pioneered basic and applied research on occupational hearing risks and preventive measures. The Institute has issued recommendations and promoted effective interventions through mechanisms ranging from formal criteria documents to blogs and social media. NIOSH has conducted surveillance and published statistics to guide policy and target prevention efforts. Over the past five decades, substantial progress has been made in raising awareness of noise as a hazard, reducing the risk of occupational hearing loss, improving the use of hearing protection, and advancing measurement and control technologies. Nevertheless, noise remains a prevalent workplace hazard and occupational hearing loss is still one of the most common work-related conditions. NIOSH continues to work toward preventing the effects of noise and ototoxicants at work and has many resources to assist audiologists in their hearing loss prevention efforts.
Keywords: NIOSH; history; noise exposure; occupational hearing loss; hearing loss prevention; hearing protection; surveillance; ototoxicity